Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1051/matecconf/201926504015
|View full text |Cite
|
Sign up to set email alerts
|

Strength assessment of earth dams

Abstract: A comparative method for estimating the stress-strain state of earth dams under the effect of static load is given in the paper using spatial and plane-strain models. The results of assessment of stress-strain state of several earth dams using these methods are given. Analysis of the results obtained allows us to conclude that a plane calculation model gives results almost identical to the ones obtained with spatial model; in future that can be the basis for developing recommendations on the use of certain cal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 5 publications
(6 reference statements)
0
2
0
Order By: Relevance
“…, the solution of which satisfying the boundary conditions of the problem by the Bubnov-Galerkin method, is sought in the form [16][17][18][19][20]:…”
Section: The Methods Of Solutionmentioning
confidence: 99%
“…, the solution of which satisfying the boundary conditions of the problem by the Bubnov-Galerkin method, is sought in the form [16][17][18][19][20]:…”
Section: The Methods Of Solutionmentioning
confidence: 99%
“…-in [45,47], the stress state and natural oscillations of two earth dams in a spatial setting were studied. When assessing the strength, some dangerous sections of the dam were identified and natural frequencies were found that were not taken into account using a plane model;…”
Section: Introductionmentioning
confidence: 99%